2017
DOI: 10.1155/2017/8459287
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin, the Main Active Ingredient of Shuyu Capsule, Inhibits Cav1.2 and Regulates Calmodulin/Calmodulin-Dependent Protein Kinase II Signalling

Abstract: The aim of this study was to explore the mechanism underlying the antidepression activity of paeoniflorin, the main active ingredient of paeony extract and Shuyu capsules, and determine its effect on the calmodulin/calmodulin-dependent protein kinase II (CaM/CaMKII) signalling pathway and on the possible target, the voltage-gated calcium channel (Cav). Rats at the nonacceptance stage were selected for premenstrual syndrome (PMS) depression modelling. Behavioural assays were used for model testing. Rats were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Cacna1a also serves as a key gene in the GABA synapse pathway and dopamine synapse pathway, so it can be deduced that BXD can influence various signal pathways in the central nervous system by acting on genes for calcium ion pathway protein, thus realizing the treatment of PMDD irritability. The signaling pathways through Ca 2+ channels was described in our previous report, in which we found that paeoniflorin, one of the active compounds of BXD, could inhibit one of the subtypes of the Ca 2+ channels ( Song et al, 2017 ).…”
Section: Discussionmentioning
confidence: 70%
“…Cacna1a also serves as a key gene in the GABA synapse pathway and dopamine synapse pathway, so it can be deduced that BXD can influence various signal pathways in the central nervous system by acting on genes for calcium ion pathway protein, thus realizing the treatment of PMDD irritability. The signaling pathways through Ca 2+ channels was described in our previous report, in which we found that paeoniflorin, one of the active compounds of BXD, could inhibit one of the subtypes of the Ca 2+ channels ( Song et al, 2017 ).…”
Section: Discussionmentioning
confidence: 70%
“…Paeoni orin has neuroprotective and antidepressant biological activities, and it can treat related insomnia diseases through adenosine A1R to play a hypnotic effect [36]. Regulating the calmodulin/calmodulin-dependent protein kinase II (CaM/CaMKII) pathway and its downstream signaling molecules play an important role in the treatment and alleviation of affective disorders [37]. Glycyrrhizin can reduce IL-6 cytokines in brain tissue, and it is also a cytokine closely related to sleep/deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…The voltage stimulation scheme of the whole cell patch clamp recording GABA current was as follows [40]: after formation of the whole cell seal, the cell membrane voltage was clamped at −70 mV and the cell surface injected with 30 µM GABA, 10 µM Str, and 300 nm TTX. The peak value of the current was recorded in the gap-free mode.…”
Section: Whole-cell Patch Clampmentioning
confidence: 99%